2005
DOI: 10.1123/jsm.19.4.480
|View full text |Cite
|
Sign up to set email alerts
|

A Typology of Approaches to Comparative Analysis of Sports Policy

Abstract: This article provides a four-fold typology of comparative sports policy studies: Type 1, Seeking Similarities, is a nomothetic approach seeking law-like generalization; Type 2 is Describing Difference, an ideographic approach seeking to capture the specificity of policy systems; Type 3, Theorizing the Transnational, goes beyond the nation-state as the unit of analysis to fuse global and local levels of explanation; and Type 4, Defining Discourse, seeks to analyze ways in which policy discourse defines the real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 16 publications
0
29
0
2
Order By: Relevance
“…Mixed research methods were used for several purposes and at several levels: a sequential exploratory research and as part of this, a triangulation method. These methods were also suggested by Henry et al (2005) to address in part the problems associated with cross-national research. The unique feature of this study is that in addition to measuring the easily quantifiable variables, it assesses processes by means of an elite sport climate survey (both objective and subjective data) with the main stakeholders in elite sport.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mixed research methods were used for several purposes and at several levels: a sequential exploratory research and as part of this, a triangulation method. These methods were also suggested by Henry et al (2005) to address in part the problems associated with cross-national research. The unique feature of this study is that in addition to measuring the easily quantifiable variables, it assesses processes by means of an elite sport climate survey (both objective and subjective data) with the main stakeholders in elite sport.…”
Section: Discussionmentioning
confidence: 99%
“…Henry et al (2005) identified four types of comparative analysis on sport policies, each accompanied with their specific weaknesses and core problems. The types of comparative analysis reveal difficulties related to operationalization, comparability, measurement, explanations of causality, validation, reliability, interpretation, moving beyond the descriptive, and balancing between global and local factors.…”
Section: The Complexity Of Cross National Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, researchers who place sport management within the material contexts of everyday life and multi-racial, economic and political democracy can, as Henry, Amara, Al-Tauqi, and Lee (2005) maintain, effectively address the imperatives of consumption; the dynamics of the marketplace; commercial space; the sweeping reach of neo-liberal ideology, power and influence; the production of knowledges and identities; nation-states; globalization; freedom; and community (Henry et al, 2005). They articulate the importance of international sports policy development and governance and the corresponding need for sustained comparative analysis.…”
Section: Personal Point Of Entrymentioning
confidence: 99%